Antarctic ozone depletion chemistry - Reactions of N2O5 with H2O and HCl on ice surfaces - Tolbert, Margaret A.; Rossi, Michel J.; Golden, David M. (1988)
In a study concerning Antarctic ozone depletion, reactions of dinitrogen pentoxide with water and hydrochloric acid were studied on ice surfaces in a Knudsen cell flow reactor. The N2O5 reacted on ice at 185 K to form condensed-phase nitric acid (HNO3). This reaction may provide a sink for odd nitrogen, NO(x), during the polar winter, a requirement in nearly all models of Antarctic ozone depletion. The reaction of N2O5 on HCl-ice surfaces at 185 K produced gaseous nitryl chloride (ClNO2) and condensed-phase HNO3 and proceeded until all of the HCl within the ice was depleted. The ClNO2 which did not react or condense on ice at 185 K, can be readily photolyzed in the Antarctic spring to form atomic chlorine for catalytic ozone destruction cycles. The other photolysis product, gaseous nitrogen dioxide may be important in the partitioning of NO(x) between gaseous and condensed phases in the Antarctic winter.